2020
DOI: 10.1007/s11524-020-00461-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Opportunities for Spiritual and Religious Supports to Improve HIV-Related Outcomes for Black Sexual Minority Men

Abstract: Given the importance of spirituality and religion in the lives of many Black gay, bisexual, and other Black sexual minority men (SMM) and the need for additional resources to improve HIV outcomes within this population, research on how spiritual and religious support can promote HIV prevention and treatment among Black SMM is greatly needed. We conducted nine focus groups with 52 spiritual and religious Black SMM in Baltimore, Maryland, to explore opportunities for HIV-related programming that incorporates spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…Although this programming is potentially beneficial, it may inadvertently narrow the focus on Black SGL men to issues of pathology. Alternatively, some Black SGL men have expressed a desire for more spiritual support in nonreligious settings (Grieb et al, 2020). Black SGL male-led spiritual organizations like ADODI are already doing this work.…”
Section: Discussionmentioning
confidence: 99%
“…Although this programming is potentially beneficial, it may inadvertently narrow the focus on Black SGL men to issues of pathology. Alternatively, some Black SGL men have expressed a desire for more spiritual support in nonreligious settings (Grieb et al, 2020). Black SGL male-led spiritual organizations like ADODI are already doing this work.…”
Section: Discussionmentioning
confidence: 99%
“…However, many BMSMs report a strong desire for spiritual and religious engagement outside religious institutions. 19 The finding that spirituality, which can be practiced in private, may be more salient than physical religious participation in public spaces suggests that spirituality may offer an opportunity to engage the protective aspects of these sociocultural factors without increasing exposure to HIV stigma.…”
Section: Discussionmentioning
confidence: 99%
“…17 Spirituality was shown in one study to mitigate HIV risk by reducing BMSM's internalization of homonegativity, which was related to a higher likelihood of using condoms during insertive anal sex. 18 Another possible mechanism is that spirituality may help men strengthen their faith in something greater than themselves and motivate them to adhere to their ART medications, 19 which lowers the risk of transmitting HIV to others. 20 Black people, compared with people of other races and ethnicities, regardless of other intersecting social identities (e.g., gender identity, sexual orientation, and age), have a higher frequency of religious engagement and consider religion salient in their lives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Black Americans have also shown positive religious coping significantly predicted medication adherence [69]. Studies have also shown mixed results with Black MSM regarding the role of religion and spirituality in HIV prevention and outcomes, with both positive and negative effects [70,71]. Further research is needed to elucidate what aspects of religion and spirituality are effective in improving HIV prevention and outcomes.…”
Section: Religion and Spiritualitymentioning
confidence: 99%